Experimental Study of Condenser Performance for Solar Energy Driven Adsorption Cycle Refrigeration - Ben Marto Siallagan (International Journal of Mechanical Computational and Manufacturing Research, 2020)
The condenser is one component of the refrigeration machine that can change the fluid phase and can exchange heat. The condenser, collector and evaporator are part of the cooling machine that is designed to be a prototype machine. In this design specifically the author is in charge of designing and manufacturing and testing the condenser. The cooling machine consisting of a collector/generator that uses activated carbon functions to absorb and store solar energy. The evaporator which uses methanol functions to absorb the surrounding heat. This cooling machine is driven by solar energy using an adsorption cycle process. The collector/generator that has been heated to solar energy will absorb the methanol contained in the evaporator and the methanol also absorbs all the surrounding heat so that the water temperature gets lower. The condersor in this design functions to change the vapor phase methanol in the collector which will be condensed into a liquid phase which is then flowed to the evaporator. From this design produces an adsorption cycle cooling machine that is driven by solar energy.